Valuing mangrove-fishery linkages: A case study of Campeche, Mexico - Edward B. Barbier; Ivar E. Strand (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper explores the value of mangrove systems as a breeding and nursery habitat for off-shore fisheries, focusing on mangrove-shrimp production linkages in Campeche State, Mexico. We develop an open access fishery model to account explicitly for the effect of mangrove area on carrying capacity and thus production. From the long-run equilibrium conditions of the model we are able to establish the key parameters determining the comparative static effects of a change in mangrove area on this equilibrium. We then estimate empirically the effects of changes in mangrove area in the Laguna de Terminos on the production and value of shrimp harvests in Campeche over 19890-90. Our findings suggest that mangroves are an important and essential input into the Campeche shrimp fishery, but that low levels of deforestation between 1980 and 1990 mean that the resulting losses to the shrimp fishery are still comparatively small. Over-exploitation of the fishery due to open access conditions remains the more pervasive threat, and without better management, any long-run benefits of protecting mangrove habitat are likely to be dissipated.
Keywords: Q2; Q12; 330; Bioeconomic; Campeche; Deforestation; Ecological; Economic; Fishery; Habitat; Harvest; Laguna de Terminos; Mangrove; Mexico; Open access; Shrimp; Fischerei; Entwaldung; Theorie; Campeche (Staat)